The Impact of Learner Ill-Discipline on Teaching and Learning in High Schools of Waterberg District, Limpopo Province - Mashaba Ernest Khalabai; Ntshengedzeni Albert Tshisevhe; Simeon Maile (E-Journal of Humanities, Arts and Social Sciences)
Studies have indicated that lack of discipline among learners in schools is one of the foremost problems facing schools both nationally and internationally. This paper thus investigated the causal factors of learner ill-discipline at the school level with the intention to come up with practical measures that can be applied by the schools to curb learner indiscipline. The qualitative method with a case study approach was used to conduct an in-depth investigation into the phenomenon of learner indiscipline. Three high schools in the Bela-Bela township were sampled as participants for the study. Data was collected through one-on-one semi-structured interviews and document analyses on learner code of conduct and school disciplinary policy. Three (3) school principals, six (6) teachers and six (6) learners were interviewed. The findings revealed that schools are characterised by rampant levels of learner ill-discipline with a negative impact on teaching and learning. The study argued that two primary factors fuelling learner ill-discipline in schools are the inappropriate implementation of the learner code of conduct and the school disciplinary policy. It concluded that there is an urgent need for proper implementation of the learner code of conduct and the disciplinary policy in the schools. This study strongly recommends that education authorities put measures in place to ensure that schools comply with the proper implementation of the code of conduct and school disciplinary policy. The findings of this study contribute to a discourse in the body of knowledge in learner discipline.